(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Scleroderma (Systemic Sclerosis, SSc) is a chronic autoimmune connective tissue disease characterized by progressive fibrosis of the skin and internal organs, vasculopathy, and immune system dysregulation. In neonates, this condition is exceedingly rare and diagnostically challenging, frequently being confused with similar entities — sclerema neonatorum, scleredema, and subcutaneous fat necrosis (SCFN). This article provides a detailed review of the etiological factors, pathogenetic mechanisms, and clinically relevant risk factors of neonatal scleroderma. In particular, the roles of genetic susceptibility, maternal-fetal immunological interactions (microchimerism), infectious agents, and environmental influences are analyzed.